PENGARUH LITERASI KEUANGAN DAN PERILAKU KEUANGAN TERHADAP KEPUTUSAN INVESTASI MAHASISWA - Siregar, Dina Khairuna; Anggraeni, Desfi Rahma (Bussman Journal : Indonesian Journal of Business and Management, 2022)
Every investment requires the right decision because this decision will affect investment results in the future. People’s access to financial products and services that continue to increase and are so easily available does not have a positive impact, especially on the younger generation if they do not have good financial understanding and management. The purpose of this study was to determine the effect of financial literacy and financial behavior on investment decisions of students majoring in Accounting FEB Bina Bangsa University. The research method used is a quantitative method using a questionnaire using a judgment sampling technique which was distributed to 62 respondents. The data analysis technique used is multiple regression test, t test and F test using SPSS Software Version 25. The results of this study show that financial literacy has a significant positive effect on investment decisions. The higher a person’s financial literacy knowledge, it will affect investment decisions. The results of this study also found that student financial behavior has a significant positive effect on investment decisions. The higher the financial behavior such as the management of financial planning and financial irregularities, the easier it will be for someone to invest